2017
DOI: 10.1080/15592294.2017.1320637
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to neurotoxic metals is associated with increased placental glucocorticoid receptor DNA methylation

Abstract: Epigenetic alterations related to prenatal neurotoxic metals exposure may be key in understanding the origins of cognitive and neurobehavioral problems in children. Placental glucocorticoid receptor (NR3C1) methylation has been linked to neurobehavioral risk in early life, but has not been examined in response to neurotoxic metals exposure despite parallel lines of research showing metals exposure and NR3C1 methylation each contribute to a similar set of neurobehavioral phenotypes. Thus, we conducted a study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 59 publications
2
35
0
1
Order By: Relevance
“…The gene which encodes for GR, NR3C1 contains nine exon 1 variants and methylation of the promoter region of these variants likely regulates which isoforms are expressed. Recent research has demonstrated that maternal exposure to a range of trace elements can regulate methylation of NR3C1 which is often linked to neurodevelopmental disorders in children . This study demonstrated that the methylation status of placental NR3C1 is increased by trace elements such as cadmium and manganese while low levels of zinc were also associated with increased methylation .…”
Section: Key Placental Mechanisms Linking Maternal Deficits In Micronmentioning
confidence: 57%
See 2 more Smart Citations
“…The gene which encodes for GR, NR3C1 contains nine exon 1 variants and methylation of the promoter region of these variants likely regulates which isoforms are expressed. Recent research has demonstrated that maternal exposure to a range of trace elements can regulate methylation of NR3C1 which is often linked to neurodevelopmental disorders in children . This study demonstrated that the methylation status of placental NR3C1 is increased by trace elements such as cadmium and manganese while low levels of zinc were also associated with increased methylation .…”
Section: Key Placental Mechanisms Linking Maternal Deficits In Micronmentioning
confidence: 57%
“…Recent research has demonstrated that maternal exposure to a range of trace elements can regulate methylation of NR3C1 which is often linked to neurodevelopmental disorders in children . This study demonstrated that the methylation status of placental NR3C1 is increased by trace elements such as cadmium and manganese while low levels of zinc were also associated with increased methylation . The placenta limits foetal exposure to glucocorticoids through the actions of the enzyme, 11‐beta‐hydroxysteroid dehydrogenase 2 (HSD‐11β2).…”
Section: Key Placental Mechanisms Linking Maternal Deficits In Micronmentioning
confidence: 89%
See 1 more Smart Citation
“…In a second study to look at the epigenetic effects of lead exposure, prenatal lead exposure was associated with increased placental glucocorticoid receptor ( NR3C1 ) methylation in healthy, singleton newborns (Appleton, Jackson, Karagas, & Marsit, ). These findings are intriguing, given that this group found that increased methylation of a factor score defined by CpG sites on NR3C1 increased the odds that a newborn would be difficult to soothe, highly aroused, and poorly self‐regulated (Paquette et al., ).…”
Section: Potential Mechanisms Of Lead Exposurementioning
confidence: 99%
“…Another recent study has demonstrated that among 16 measured chemicals, CB-105 was identified as the most “epigenetically active” pollutant for female newborns [117]. One of our prior studies has investigated a positive association of co-action between prenatal metals exposure assessed by a cumulative risk score (higher scores represent greater cumulative metals exposure risk) with placental NR3C1 methylation [24], which suggested multiple metals exposure jointly exert accumulated epigenetic impacts. Demethylation of AHRR in the cord blood of children with prenatal smoking exposure is broadly reported.…”
Section: Challenges and Outlookmentioning
confidence: 99%